If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + 1) = 18 Reorder the terms: 6(1 + 2x) = 18 (1 * 6 + 2x * 6) = 18 (6 + 12x) = 18 Solving 6 + 12x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 12x = 18 + -6 Combine like terms: 6 + -6 = 0 0 + 12x = 18 + -6 12x = 18 + -6 Combine like terms: 18 + -6 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| q^2-8q+12=0 | | 2X-2=4+2x | | 7n+6=7n+6 | | x+1=8x+15 | | 0.1x+0.3x+6=2 | | 3(2x-6)=4(x-12) | | 9(a-3)+15=33 | | 42=18-4m | | 2e^4*x=17 | | 6x+5-2(-3x-4)=2(x-1) | | 2.1k=12.81 | | 2=4(3k+-8)+-11k | | y/4=3 | | 3a(5-21)b=1+2i | | -11=-4+7x+1 | | 2g+3+4g=-3(17+7g) | | t/9=16 | | -7(z-5)-(4+4z)=-12z | | h/72=-20 | | 20h=-72 | | 4f-2f^2=100 | | -5(3x-4)+5x=2(x+2) | | 5x^2-5x-30/10x-30 | | 4(x+2)-3x+5=x+4 | | -2x+6+4x=24 | | x^5-2x^4-x+2=0 | | (a^3+a^2+a)/(a-1) | | h+(-72)=-20 | | 2+4x=7x+26 | | 3(x+3)-2x+4=x+5 | | (a^3+a^2+a)/a-1 | | 8x(5+3)= |